Persepsi Karyawan Keuangan Terhadap Efektivitas Kinerja Pasca Implementasi ERP SAP di PT Perkebunan Nusantara I Regional 4 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the perceptions of finance employees regarding performance effectiveness after implementing SAP HANA-based ERP at PT Perkebunan Nusantara I Regional 4. A descriptive qualitative method was used, involving semi-structured interviews and direct observation. The results show that ERP-SAP positively impacts recording efficiency, reporting accuracy, reconciliation ease, and regulatory compliance. The system also improves data access speed, reduces manual input errors, and supports real-time data integration across departments. Positive user perception is a crucial factor in the success of the ERP system implementation.